The Role of the Secondary Sector in Poverty Alleviation in Indonesia - Nurfika; Jean-Claude Maswana (The Journal of Indonesia Sustainable Development Planning, 2021)
The relationship between economic growth and poverty reduction, although well established, is heterogeneous. The heterogeneity stems not only from socio-economic factors but also from the structure of output growth. In Indonesia, the secondary sector seems to be less poverty-reducing than other sectors. This study examines the impact of sectoral growth on poverty in Indonesia, with particular attention to the disaggregated secondary sector, and also analyzes the relative sensitivities of poverty reduction to the labor-intensive and non-labor-intensive sectors. The empirical analysis uses provincial panel data on Indonesia for the period 2003–2018 and employs the pooled OLS method. The results show that sectoral growth has little effect on improving the condition of the poor in Indonesia. Nevertheless, this conclusion has a high potential to be inappropriate. Perhaps a better conclusion on the linkage between sectoral growth and poverty can be drawn if the characteristics of mining-driven and nonmining-driven provinces in Indonesia are taken into account. In nonmining-driven provinces, the secondary sector pales in comparison to services in alleviating poverty. Six-sector disaggregation of the economy (with or without controlling for the distributional effect through labor intensity) reveals that, within the secondary sector, the subsectors that significantly reduce poverty in nonmining-driven provinces are mining and construction. Mining-driven provinces, however, do not display a linkage between sectoral growth and poverty. The significant role of labor intensity in determining whether sectoral growth is pro-poor suggests that adopting policies that lean toward discouraging businesses from employing labor is inadvisable.